1993
DOI: 10.1111/j.2044-8341.1993.tb01736.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive therapy for depression with individuals with intellectual disabilities

Abstract: The increase in research into psychopathology in people with intellectual disability has recently spread to include depression. Several reports have appeared on the assessment of depression in the client group and there is a pressing need for research into treatment of depression in people with intellectual disability. The present paper reviews cognitive behaviour therapy for depression and reports on its adaptation for people with intellectual disability. Two case studies of individuals with mild intellectual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 4 publications
1
60
0
1
Order By: Relevance
“…The Zung Depression Scale (Zung, 1965) was chosen because it has been adapted for people with intellectual disability (adapted Zung; Kazdin et al, 1983) and is commonly used in research with this population Lindsay et al, 1993). It has 19 questions with yes/no answers covering a range of depressive symptoms-for example 'Morning is when I feel best'.…”
Section: Measures and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The Zung Depression Scale (Zung, 1965) was chosen because it has been adapted for people with intellectual disability (adapted Zung; Kazdin et al, 1983) and is commonly used in research with this population Lindsay et al, 1993). It has 19 questions with yes/no answers covering a range of depressive symptoms-for example 'Morning is when I feel best'.…”
Section: Measures and Designmentioning
confidence: 99%
“…Lindsay, Michie, Baty, Smith, and Miller (1994) and Reynolds & Baker (1988) reported high correlation between measures of depression, which included cognitive items. In addition, the clinical application of cognitive techniques in this client group has begun to be demonstrated for a range of conditions (Chiodo & Maddux, 1985;Howells, Rogers, & Wilcock, 2000;Lindsay, Neilson, & Smith, 1998), including depression (Lindsay, Howells, & Pitcaithly, 1993). These studies suggest that cognitive factors can be assessed in people with intellectual disability with sufficient reliability for clinical use.…”
Section: Introductionmentioning
confidence: 97%
“…However, the use of psychotherapy has been suggested in the mildly retarded [34], and there is at least one article suggesting that a modification of cognitive therapy was efficacious in two depressed mentally retarded individuals [35]. Regarding biological treatments, Puri et al [36] and Kessler [37] reported on sparse literature suggesting that electroconvulsive therapy (ECT) is efficacious in depressed mentally retarded individuals.…”
Section: Treatment Of Depressionmentioning
confidence: 98%
“…The success of CBT as an effective intervention has encouraged clinicians and researchers to investigate and apply its techniques in a wide range of clinical problems; these include depression (for a review, see Watkins & Williams, 1998), panic (Clark et al, 1994), psychotic symptoms (Garety et al, 1994) and personality disorder (Nelson-Gray & Farmer, 1999). More recently, the efficacy of CBT as a treatment for adults with mild learning disability has been established (Lindsay et al, 1993), although, to date, sample sizes have been small.…”
Section: Cognitive-behavioural Therapymentioning
confidence: 99%